2013
DOI: 10.1186/1471-2458-13-384
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in migrant preschool children

Abstract: BackgroundMinority groups have a lower health-related quality of life (HRQOL), but there is little information if this finding also applies to children. In this study, we compared HRQOL between young children with and without migrant parents.MethodsTwo cross-sectional studies of culturally diverse preschool populations in Switzerland: Ballabeina (40 preschools, 258 girls and 232 boys aged 4 to 6 years) and Youp’là Bouge (58 child care centers, 453 girls and 522 boys aged 2 to 4 years). Most children were born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…Few studies have examined the relationship between health-related quality of life and screen media use among preschool children. Among the few, Puder et al (2013) reported that when compared to non-migrant preschool children, preschool children from migrant families living in two different regions in Switzerland, have significantly lower PedsQL™ total score, in one region but not in the other. Importantly, Puder et al (2013) reported that the most relevant confounders of their findings were parental education, paternal occupation, child screen time and child BMI.…”
Section: Health-related Quality Of Life and Meeting The Who Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the relationship between health-related quality of life and screen media use among preschool children. Among the few, Puder et al (2013) reported that when compared to non-migrant preschool children, preschool children from migrant families living in two different regions in Switzerland, have significantly lower PedsQL™ total score, in one region but not in the other. Importantly, Puder et al (2013) reported that the most relevant confounders of their findings were parental education, paternal occupation, child screen time and child BMI.…”
Section: Health-related Quality Of Life and Meeting The Who Guidelinesmentioning
confidence: 99%
“…Among the few, Puder et al (2013) reported that when compared to non-migrant preschool children, preschool children from migrant families living in two different regions in Switzerland, have significantly lower PedsQL™ total score, in one region but not in the other. Importantly, Puder et al (2013) reported that the most relevant confounders of their findings were parental education, paternal occupation, child screen time and child BMI. The screen time reported for children aged 5-7 years was 31 ± 30, 37 ± 35 and 52 ± 49 min per day, respectively for families with both parents who were non-migrants, one parent and both parents who were migrants.…”
Section: Health-related Quality Of Life and Meeting The Who Guidelinesmentioning
confidence: 99%
“…Studies on migrant preschool children living in Switzerland [53] and in Germany [54] proved that exposure to traumatic stimuli in a new living environment can have a significant negative impact on their HRQoL and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies reporting the QOL-adiposity relation in children are predominantly cross-sectional [26][27][28]. Longitudinal studies are warranted to elucidate psychosocial QOL-related changes in adiposity since the opposite direction might also be true, i.e.…”
Section: Adiposity As Outcomementioning
confidence: 99%
“…Most studies on the association between QOL and adiposity in children were cross-sectional [26], some of them found an inverse relation and some of them found no significant relation. Also, in preschoolers, the cross-sectional association between adiposity and QOL has been described [27,28] with overweight children having a lower school and social QOL. Nevertheless, the few longitudinal studies conducted in children and adolescents did not reveal clear effects of QOL on adiposity.…”
Section: Introductionmentioning
confidence: 99%